Cardiac remodelling and dysfunction in children with obstructive sleep apnoea: a community based study. Issue 3 (13th November 2008) - Chan, J Y S; Li, A M; Au, C-T; Lo, A F C; Ng, S-K; Abdullah, V J; Ho, C; Yu, C-M; Fok, T-F; Wing, Y-K
Abstract : Background: Childhood obstructive sleep apnoea (OSA) is suggested to be associated with cardiac structural abnormalities and dysfunction but existing evidence is limited and the treatment effect on echocardiographic outcome remains controversial. Objective: To examine the presence of subclinical cardiac abnormalities in childhood OSA and the effects of treatment on cardiac changes. Methods: Polysomnography (PSG) and echocardiographic examinations were performed in 101 children aged between 6 and 13 years who were invited from a community based questionnaire survey. They were classified into a reference group (apnoea–hypopnoea index (AHI) <1, n = 35), mild OSA group (AHI 1–5, n = 39) and moderate to severe group (AHI >5, n = 27) based on the PSG results. Treatments, including adenotonsillectomy or nasal steroids, were offered to the mild and moderate to severe OSA groups. Results: The moderate to severe OSA group had greater right ventricular (RV) systolic volume index (RVSVI), lower RV ejection fraction (RVEF) and higher RV myocardial performance index (RVMPI) than the reference group. They also had more significant left ventricular (LV) diastolic dysfunction and remodelling with larger interventricular septal thickness index (IVSI) and relative wall thickness than those with lower AHI values. The moderate to severe OSA group had an increased risk of abnormal LV geometry compared with the reference group (odds ratio 4.21 (95% CI 1.35 to 13.12)). Log transformed AHI was associated with RVSVI (p = 0.0002), RVEF (p = 0.0001) and RVMPI (p<0.0001), independent of the effect of obesity. Improvement in RVMPI, IVSI and E/e′ were observed in those with a significant reduction in AHI (>50%) comparing 6 month with baseline data. Conclusions: OSA is an independent risk factor for subclinical RV and LV dysfunction, and improvement in AHI is associated with reversibility of these abnormalities.